An Adaptation of Motivational Interviewing Increases Quit Attempts in Smokers With Serious Mental Illness - Steinberg, Marc L. (Nicotine Tob Res, 2016)
INTRODUCTION: Smokers with serious mental illness (SMI) have a high smoking prevalence and a low quit rate. Motivational interviewing (MI) is an empirically supported approach for addressing substance use disorders and may motivate smokers with SMI to quit. METHODS: We randomized smokers (N = 98) with SMI to receive a single 45-minute session of (1) MI with personalized feedback or (2) interactive education. We hypothesized that participants receiving the MI intervention would be more likely to follow-up on a referral for tobacco dependence treatment, to make a quit attempt, and to quit smoking than those receiving the interactive educational intervention. RESULTS: Smokers receiving an MI intervention were significantly more likely to make a quit attempt by the 1-month follow-up (34.7% vs. 14.3%; OR = 4.39 [95% CI = 1.44 to 13.34], P = .009); however, these quit attempts did not translate into abstinence. In addition, 32.7% of those receiving MI followed-up on a referral for tobacco dependence treatment (vs. 20.4% receiving interactive education; OR = 2.02 [95% CI = 0.76 to 3.55], P = .157). MI Treatment Integrity Code ratings indicated that the interventions were easily distinguishable from each other and that MI was delivered with proficiency. Despite the intervention’s brevity, participants reported high levels of therapeutic alliance with their therapist. CONCLUSIONS: A brief adaptation of MI with personalized feedback appears to be a promising approach for increasing quit attempts in smokers with SMI, but future research is required to determine how to best help smokers with SMI to attain sustained abstinence.